L-Type amino acid transporter 1 activity of 1, 2, 3-triazolyl analogs of l-histidine and l-tryptophan. Issue 16 (15th August 2019) - Hall, Colton; Wolfe, Hannah; Wells, Alyssa; Chien, Huan-Chieh; Colas, Claire; Schlessinger, Avner; Giacomini, Kathleen M.; Thomas, Allen A.
Graphical abstract: Abstract: A series of 1, 2, 3-triazole analogs of the amino acids l -histidine and l -tryptophan were modeled, synthesized and tested for l -type amino acid transporter 1 (LAT1; SLC7A5) activity to guide the design of amino acid-drug conjugates (prodrugs). These triazoles were conveniently prepared by the highly convergent Huisgen 1, 3-dipolar cycloaddition (Click Chemistry). Despite comparable predicted binding modes, triazoles generally demonstrated reduced cell uptake and LAT1 binding potency relative to their natural amino acid counterparts. The structure-activity relationship (SAR) data for these triazoles has important ramifications for treating cancer and brain disorders using amino acid prodrugs or LAT1 inhibitors.